International Journal of Environment and Climate Change - Nyaga, Justine M.; Nyaga, Samuel K.; Gathungu, Geofrey K.; Njeru, Jafford R. (My University, 2020)
Africa is under pressure from climate stresses and is highly vulnerable to the impacts of climate change. In Kenya, agriculture is the backbone of the economy making it an important contributor to food security of rural households. Currently crop productivity is being affected by continued climate variations and decline in soil fertility. Adaptation to climate change requires to be given high and urgent priority for sustainable crop production. A study was conducted in Mavuria ward, Mbeere South Sub-County, Embu County to evaluate the effects of climate change adaptation on crop production. The study used both descriptive and experimental research designs. The primary data on adaptation measures was collected from farmers and institutions using questionnaires. In the data analysis, descriptive statistics were used to organize the climate data and that of the respondents into frequencies. Further, a Pearson correlation test was done to determine the relationship between farmer and institutional based mechanisms on adaptation to climate change at α=0.05. The main adaptation mechanisms identified were soil fertility improvement, soil and water conservation, early planting, pest and disease control, provision of certified seeds, and awareness creation. In view of these findings, the study recommends continuous implementation of these measures that can help strengthen farmers and institutional adaptation mechanisms towards climate change for improved crop production.
Effect of Institutional and Farmer Based Climate Change Adaptation Measures on Crop Production in Mavuria Ward, Mbeere South Sub-county, Embu County, Kenya
Keywords: Climate change; crop production; farmers; institutions; Adaptation measures